2013
DOI: 10.1038/nchembio.1293
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the functional yeast ABC transporter interactome

Abstract: ABC transporters are a ubiquitous class of integral membrane proteins of immense clinical interest because of their strong association with human disease and pharmacology. To improve our understanding of these proteins, we used Membrane Yeast Two-Hybrid (MYTH) technology to map the protein interactome of all non-mitochondrial ABC transporters in the model organism Saccharomy cescerevisiae, and combined this data with previously reported yeast ABC transporter interactions in the BioGRID database to generate a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 48 publications
2
77
0
Order By: Relevance
“…A novel S. cerevisiae glutathione exporter ABC protein (Adp1 or Gxa1p) was recently characterized (Kiriyama et al 2012), and has subsequently been located in the vacuole (Snider et al 2013). The role of this transporter in polyfunctional thiol release remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A novel S. cerevisiae glutathione exporter ABC protein (Adp1 or Gxa1p) was recently characterized (Kiriyama et al 2012), and has subsequently been located in the vacuole (Snider et al 2013). The role of this transporter in polyfunctional thiol release remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study of the PPIs involved in the HOG pathway is important for determining the methods by which proteins come together to mediate a proper cellular reaction to extracellular stress. In this study, we took advantage of the MYTH method in budding yeast, already proven to be useful in the elucidation of protein interactors of several yeast and human integral membrane proteins [22,24,26], to search for physical interactors of Sho1p, and therefore find additional regulators of the Sho1p branch of the HOG pathway. Using the MYTH method, along with two other complementary PPI assays, we generated for the first time a high-quality Sho1p interactome, which includes 40 novel Sho1p interactors.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown, lysed, immunoprecipitated, and Western blotted with rabbit anti-HA antibody as previously described [24]. …”
Section: Methodsmentioning
confidence: 99%
“…Paumi et al (2007) reported the identification of six potential partners of the yeast ABC transporter of the ABCC subclass, YCF1 (Yeast Cadmium Factor1). In a follow-up report, the same consortium provided the first yeast ABC interactome by analyzing 19 of all 22 yeast ABC transporters (Snider et al 2013). An unexpected outcome was the large number of functionally diverse interactors.…”
Section: Toward An Identification Of Abc Transporter Interactomes Durmentioning
confidence: 99%